The Prevalence of Age-Related Eye Diseases and Cataract Surgery among Older Adults in the City of Lodz, Poland - Michal Szymon Nowak; Janusz Smigielski (Journal of Ophthalmology)
Purpose. To determine the prevalence of age-related eye diseases and cataract surgery among older adults in the city of Lodz, in central Poland. Material and Methods. The study design was cross-sectional and observational study. A total of 1107 women and men of predominantly Caucasian origin were successfully enumerated and recruited for the study. All selected subjects were interviewed and underwent detailed ophthalmic examinations. Results. Overall 8.04% (95% CI 6.44–9.64) subjects had cataract surgery in either eye. After excluding subjects with bilateral cataract surgery, the prevalence of cataract was 12.10% (95% CI 10.18–14.03). AMD was found in 4.33% (95% CI 3.14–5.54 ) of all subjects. Of them 3.25% (95% CI 2.21–4.30 ) had early AMD and 1.08% (95% CI 0.47–1.69) had late AMD. Various types of glaucoma were diagnosed in 5.51% (95% CI 4.17–6.85) of subjects and 2.62% (95% CI 1.68–3.56) had OHT. The prevalence rates of DR and myopic macular degeneration were 1.72% (95% CI 0.95–2.48) and 0.45% (95% CI 0.06–0.85), respectively. All multiple logistic regression models were only significantly associated with older age. The highest rate of visual impairment was observed among subjects with retinal diseases. Conclusions. The study revealed high prevalence of age-related eye diseases in this older population.